DEVELOPING E-MODULES OF CONFIDENCE AT ENGLISH PUBLIC SPEAKING WITH ISLAMIC VALUES - Rakhmawati, Dian; Kayyis, Rahmatika (INOVISH JOURNAL, 2023)
Self-confidence can help someone to perform and speak well in public and is needed by a Public Speaker. These aspects of self-confidence are also actually already contained in Islam. The purpose of this research is to develop an e-module on developing self-confidence for English Public Speaking using Islamic values. The e-module development model uses ADDIE, the research sample is English education students. In this study to obtain the correct data, the authors used several methods, namely observation, interviews, questionnaires and observation sheets. The data analysis technique used in this research is descriptive data analysis technique. Based on the results of e-module validation by material experts, it can be concluded that the material in the e- module is very good. Meanwhile, based on the results of the assessment by media experts, it can also be concluded that the e-module is declared very good based on the media. In general, the quality of e-modules is good and feasible to use in the learning process at the implementation stage.